Epiphytes in Honduras: a geographical analysis of the vascular epiphyte flora and its floristic affinities to other Central American countries - Batke, Seven P. (2016)
In this paper, we compared epiphyte inventories from Honduras to recent published floristic inventories from other Central American countries including Costa Rica, Panama, Nicaragua and Belize. Previous estimates of vascular epiphytes have revealed that approximately 9 % of all global plants are epiphytes and that in some countries they constitute approximately one quarter of the total plant diversity. Early estimates of vascular epiphytes from the neotropics have mostly overestimated the total number of epiphytes at a given locality, due to systematic misconceptions and or the use of different life-form classification systems. Moreover, some Central American countries such as Honduras have so far been neglected in any epiphyte surveys. Our database for Central America included a total of 2752 flowering- plant epiphytes. We reported a total of 882 vascular epiphytes (Angiosperms and Pteridophytes) from 245 genera and 29 families from Honduras, representing 11.1 % of the country’s total vascular flora. Orchidaceae had the highest contribution to the epiphyte flora (54.9 %), followed by Polypodiaceae (18.9 %), and Bromeliaceae (11.3 %). Two distinctive floristic clusters were detected separating South-Central and North-Central countries. Honduras had the most floristic affinity to Nicaragua and Belize. In addition, a detailed floristic survey of Cusuco National Park, Honduras, a montane forest region, revealed that epiphytes in Honduras may contribute over 20 % of the total vascular flora in a particular area. The results of this study highlight the importance of epiphytes in Honduras relative to other Central American countries.